Humanismo: uma releitura existencial de Albert Camus e Jean Paul Sartre - Favero, Roberto Carlos (Universidade do Vale do Rio do Sinos, 2006)
Humanism, an existential rereading of Albert Camus and Jean-.Paul Sartre, is the subject of this presentation, which consist of a philosophical pratice of creating a possible world in this life. Believing in the humanism, is what is missing for us. We have los completely, meaning that, valuing, respecting and giving the necessary conditions for the human being became inhumane. Beliving in humanity means maily rousing humanism. Therefore, it is urgently necessary to redefine our own concept of humanism which compels us to a humanising compromise.The basic propositions of the philosophers, Camus and Sartre, as it is impossible for us to save everything, unless each individual body can be saved. That the man is a victim or cruel and not neglectin before the humanity itself. Both require a world in which crimes against humanity and at least evil, terrorism, violence, social exclusion, and prejudices will be outlawed.Sartre introduces to us freedom and an absolute value. The existentialism puts the humanity befor
Keywords: ética; existencialismo; humanismo; liberdade; responsabilidade; solidariedade; ethic; existentialism; freedom; humanism; responsibility; solidarity; Ciências Humanas